Weston's Westons portraits and nudes - Stebbins, Theodore E. Jr.; Weston, Edward 1886-1958.; Museum of Fine Arts, Boston (Boston, Massachusetts Museum of Fine Arts, 1989)
Seventy full-size plates and seventy-five smaller illustrations, all reproduced in tritone plus tinted varnish, convey the subtlety and power of the extraordinary figurative work of Edward Weston (1886-1958). This is the first major publication focusing solely upon his portraiture and nudes, offering new insights into the breadth and quality of Weston's considerable achievement. The book was published on the occasion of a major traveling exhibition of Weston's portraits and nudes organized by the Museum of Fine Arts, Boston. All the prints are drawn from the collection of William H. Lane, who acquired them from the heirs of Edward Weston.

The earliest print in the book is the palladium image Margarette Mather (1914), done in the fashionable Pictorialist style of the time. Despite winning wide acclaim for such work, in about 1920 Weston turned to an innovative Modernist style, of which Ruth Shaw (1922) is a famous example. During his years in Mexico (1923-1926), when he became a friend of Diego Rivera and other leaders of the "Mexican Renaissance," Weston produced a series of heroic portraits, including Tina Modotti (1924).
"Published on the occasion of an exhibition organized by Theodore E. Stebbins, Jr., and Carl Zahn, Museum of Fine Arts, Boston."
Cover title: Edward Weston.
Includes bibliographical references (pages 139)
Keywords: Weston, Edward -- 1886-1958 -- Exhibitions; Photography of the nude -- Exhibitions; Portrait photography -- Exhibitions; Photography, Artistic -- Exhibitions; Photographers -- California -- Biography